Observation of coupled vortex lattices in a mass-imbalance bose and fermi superfluid mixture - Yao, Xing-Can; Chen, Hao-Ze; Wu, Yu-Ping; Liu, Xiang-Pei; Wang, Xiao-Qiong; Jiang, Xiao; Deng, Youjin; Chen, Yu-Ao; Pan, Jian-Wei (Physical review letters, 2016)
Quantized vortices play an essential role in diverse superfluid phenomena. In a Bose-Fermi superfluid mixture, especially of two mass-imbalance species, such macroscopic quantum phenomena are particularly rich due to the interplay between the Bose and Fermi superfluidity. However, generating a Bose-Fermi two-species superfluid, producing coupled vortex lattices within, and further probing interspecies interaction effects remain challenging. Here, we experimentally realize a two-species superfluid with dilute gases of lithium-6 and potassium-41, having a mass ratio of about seven. By rotating the superfluid mixture, we simultaneously produce coupled vortex lattices of the two species and thus present a definitive visual evidence for the double superfluidity. Moreover, we report several unconventional behaviors, due to the Bose-Fermi interaction, on the formation and decay of two-species vortices.
Gesehen am 30.09.2021